2019
DOI: 10.1038/s41598-018-38398-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses of wheat roots inoculated with Arthrobacter nitroguajacolicus to salt stress

Abstract: It is commonly accepted that bacteria actively interact with plant host and have beneficial effects on growth and adaptation and grant tolerance to various biotic and abiotic stresses. However, the mechanisms of plant growth promoting bacteria to communicate and adapt to the plant environment are not well characterized. Among the examined bacteria isolates from different saline soils, Arthrobacter nitroguajacolicus was selected as the best plant growth-promoting bacteria under salt stress. To study the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 53 publications
4
54
1
1
Order By: Relevance
“…Similarly, upregulation of HKT family antiporters has also been reported in wheat inoculated with Serratia sp. Sl-12 [52] , Arthrobacter nitroguajacolicus [39] and maize plants treated with Bacillus amyloliquefaciens SQR9 [36] under salinity stress. Detailing the response to salinity stress in wheat by the inoculation of Enterobacter cloacae SBP-8, Singh et al [53] reported upregulation of defense related proteins by 2065%, photosynthesis related proteins by 792% and ion transport associated proteins by 765%.…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, upregulation of HKT family antiporters has also been reported in wheat inoculated with Serratia sp. Sl-12 [52] , Arthrobacter nitroguajacolicus [39] and maize plants treated with Bacillus amyloliquefaciens SQR9 [36] under salinity stress. Detailing the response to salinity stress in wheat by the inoculation of Enterobacter cloacae SBP-8, Singh et al [53] reported upregulation of defense related proteins by 2065%, photosynthesis related proteins by 792% and ion transport associated proteins by 765%.…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 99%
“… S. lycopersicum P. putida UW4 Expression of Toc GTPase Regulation of chloroplast import apparatus components [38] 13. Wheat Arthrobacter nitroguajacolicus Upregulation of AA0618700, AA0359620 , APX, GPX Expression of AA0410390, AA1982260, AA0412840 and AA1872340 Plant cell wall biosynthesis, phenylpropanoid biosynthetic pathway, glutathione-ascorbate cycle, modulation of celular osmotic balance, ROS scavenging activity [39] 14. Oryza sativa B. amyloliquefaciens SN13 Upregulation of NADP-Me2, EREBP, SOSI, BADH and SERK1 Repression of GIG and SAPK4 NADP-Me2, EREBP, SOSI, BADH and SERK1 Accumulation of MAPK5 Na + /H + antiporter system, plant growth and development, abiotic stress response, oxidative decarboxylation of L-malate, Ion homeostasis [40] 15.…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculation of A. nitroguajacolicus, the species of Arthrobacter whose 16S rRNA gene pro le is the most closely related to Ar. sp D4-14, into wheat increased the total dry weight by more than 200% in conditions of high salinity, a condition at often occurs in tandem with drought [65]. A. nitroguajacolicus demonstrated the ability to produce auxin, ACC deaminase, siderophores and solubilize phosphate [65].…”
Section: Seed Microbiomes Enrich For Microbes That Promote Root Growtmentioning
confidence: 99%
“…Several species of Streptomycetes and Bacillus cereus, B. subtilis, and B. amyloliquefaciens were well-known for their potential on plant growth promotion and biological control of phyto-pathogens. Bacterial isolates belonging to Arthrobacter conferred stress tolerance and promoted plant growth under salt stress 40 . Bt-chickpea deprived of such beneficial www.nature.com/scientificreports www.nature.com/scientificreports/ endophytic colonization may suffer under stressed field environment.…”
Section: Discussionmentioning
confidence: 99%